Keanekaragaman Hama dengan Kultur Teknis Berbeda Pada Lahan Mentimun (Cucumis Sativus) Di Desa Tanjung Seteko, Indralaya Utara, Kabupaten Ogan Ilir, Sumatera Selatan - Arsi Arsi; Rahmatul Khaira; Suparman SHK; Bambang Gunawan; Yulia Pujiastuti; Harman Hamidson; Septian Imam Nugraha; Lailatturahmi Lailatturahmi (Universitas PGRI Palembang, 2021)
There are many types of vegetables that are nutritious for health and metabolism, including cucumbers. Cucumbers are included in the vegetable category because cucumbers are often used as fresh vegetables or pickles. Cucumber cultivation is inseparable from pests and diseases. Pest management efforts must be carried out based on consideration of ecosystem stability. One of the techniques for controlling pests in cucumber plants can be done with technical culture. The research practice aims to determine the effect of technical culture on the diversity of pest types, population and intensity of cucumber pest attacks on two different fields in Tanjung Seteko Village, Inderalaya. The research was conducted with a sampling method to determine the population, intensity and pest attack. The research was carried out on two different fields of age and variety. Data analysis was performed using the t test at the 5% confidence level. Pests found in cucumber fields, namely, Aulacophora sp., Succinea sp., Valanga sp., And Leptoglossus sp. Based on observations in the field, technical culture in the village of Tanjung Seteko has a significant effect on the population and intensity of the attack of Succinea sp., Valanga sp. and Leptoglossus being Aulachopora sp. no significant effect.